An evaluation on the local government expenditure in China : productivity, efficiency and optimality - Liao, Zhaopeng (2015)
The large-scale government expenditure in China, especially the RMB 4 trillion (US $586 billion) economic stimulus plan in 2008, has raised increasing concerns over its necessity and effectiveness. This paper evaluates the effectiveness of government expenditure in China from 1995 to 2013 in three aspects: productivity, efficiency and optimality, using data extracted from official sources such as China Statistical Yearbook, Finance Yearbook of China. In light of past work, we revise and generalize Barro’s model and apply it in the context of China. We find that local government expenditure in China is productive. It is also efficient in general, despite a decreased efficiency after 2008 and a lower efficiency in western provinces. In terms of optimality, we observe that local governments have underspent before 2008 but have not underspent after 2008. Moreover, non-western provinces have underspent and western provinces have not underspent.